From Browsing to Buying: The Role of Augmented Reality in Shortening The Customer Journey in E-Commerce - Sari, Ella Shofia (Generate Digital Publishing, 2025)
Objective: This research aims to explore how Augmented Reality (AR) technology contributes to shortening the customer journey in e-commerce by enhancing product exploration, facilitating evaluation, and accelerating purchase decisions. The focus is placed on industries where product visualization is critical, namely cosmetics and furniture. Research Design & Methods: A qualitative approach was used, involving a comprehensive literature analysis and in-depth interviews with ten active users of an AR-integrated e-commerce platform. These users were purposively selected from two sectors-cosmetics and furniture-to gain insight into real user experiences across different product types. Thematic analysis was used to identify recurring patterns and behavioral tendencies. Findings: The study found that AR significantly impacts three key stages of the customer journey: product exploration, evaluation of alternatives, and final decision-making. AR increases user confidence through realistic visualizations, reduces perceived risk by providing interactive simulations, and increases engagement through control and enjoyment. In addition, AR contributes to the value of the experience, leading to greater confidence and purchase intention. Implications & Recommendations: From a managerial perspective, integrating AR into e-commerce platforms creates strategic value by shortening the buying cycle, enriching the customer experience, and strengthening brand loyalty. Businesses are advised to invest in user-friendly AR interfaces and personalize AR experiences based on user interaction data. Future research should expand to other industries and incorporate quantitative methods to validate and generalize the findings. Contribution & Value Added: This study contributes to the literature by positioning AR not only as a visualization tool but also as a strategic enabler to accelerate consumer decision-making. It adds value by bridging the gap between immersive technologies and practical marketing applications in the digital economy.